Pediatric early warning score and unplanned readmission with influenza at emergency observation room - Xu, Wanting; Liu, Anji; Xu, Wen; Zheng, Qinxin; Li, Lei; Liu, Yan; Lei, Xiaoping; Kang, Lan; Dong, Wenbin (Frontiers in Pediatrics, 2026)
BackgroundThis study explored the predictive value of the pediatric early warning scores (PEWS) in recognizing clinical deterioration and identifying children with influenza with unplanned readmission to the emergency observation room (EOR) within 72 h.MethodsA total of 196 children were included in this single-center case–control study conducted between 1 January and 30 June 2024. PEWS scores and receiver operating characteristic curves were used to evaluate the correlations between the scores and the likelihood of influenza necessitating readmission.ResultsFor each 1-point increase in PEWS score, the risk of unplanned readmission significantly increased with unadjusted PEWS of [OR 9.98 (1.54–64.73); P = 0.016] and adjusted PEWS of [OR 10.53 (3.47–31.98); P < 0.001], respectively. The time to reach the highest PEWS was significantly longer in patients who experienced unplanned readmissions (P < 0.01). Among the non-readmitted patients, 100 out of 147 (68.03%) took oseltamivir orally, compared with only 10 out of 49 (20.41%) patients with unplanned readmissions within 72 h (P < 0.001). A PEWS cutoff score of 3 indicated a relatively high sensitivity of 61.2% and specificity of 96.6%, with a positive likelihood ratio (PLR) of 18.0 and a negative likelihood ratio of 0.4.ConclusionsPEWS is potential for predicting unplanned readmissions with similar symptoms in children with influenza, demonstrating it may be an essential tool for enhancing patient care and outcomes.